Involvement of glycine receptor α1 subunits in cannabinoid-induced analgesia. (1st May 2018) - Lu, Jieping; Fan, Sijia; Zou, Guichang; Hou, Yiwen; Pan, Tao; Guo, Weiwei; Yao, Lei; Du, Feng; Homanics, Gregg E.; Liu, Dan; Zhang, Li; Xiong, Wei
Abstract: Some cannabinoids have been shown to suppress chronic pain by targeting glycine receptors (GlyRs). Although cannabinoid potentiation of α3 GlyRs is thought to contribute to cannabinoid-induced analgesia, the role of cannabinoid potentiation of α1 GlyRs in cannabinoid suppression of chronic pain remains unclear. Here we report that dehydroxylcannabidiol (DH-CBD), a nonpsychoactive cannabinoid, significantly suppresses chronic inflammatory pain caused by noxious heat stimulation. This effect may involve spinal α1 GlyRs since the expression level of α1 subunits in the spinal cord is positively correlated with CFA-induced inflammatory pain and the GlyRs antagonist strychnine blocks the DH-CBD-induced analgesia. A point-mutation of S296A in TM3 of α1 GlyRs significantly inhibits DH-CBD potentiation of glycine currents (IGly ) in HEK-293 cells and neurons in lamina I-II of spinal cord slices. To explore the in vivo consequence of DH-CBD potentiation of α1 GlyRs, we generated a GlyRα1 S296A knock-in mouse line. We observed that DH-CBD-induced potentiation of IGly and analgesia for inflammatory pain was absent in GlyRα1 S296A knock-in mice. These findings suggest that spinal α1 GlyR is a potential target for cannabinoid analgesia in chronic inflammatory pain. Highlights: DH-CBD suppresses chronic inflammatory pain in mice. The protein levels of spinal glycine receptor α1 subunits significantly increase in mice with inflammatory pain. GlyR α1 S296A mutant mice exhibit attenuated cannabinoid-analgesia.